Phenotype and psychometric characterization of Phelan-McDermid syndrome patients: pioneering towards personalized medicine - Nevado, Julián; Ciceri, Filippo; Bel-Fenellós, Cristina; Tenorio-Castaño, Jair A.; Maes, Tamara; Xaus, Jordi; Buesa, Carlos; Lapunzina, Pablo (Frontiers in Psychiatry, 2025)
IntroductionPhelan-McDermid syndrome (PMS) is a genetic disorder caused by the loss of the terminal region of chromosome 22 or by pathogenic or likely-pathogenic variants in SHANK3 gene. Individuals with PMS are affected by a variable degree of intellectual disability, delay or absence of speech, low muscle tone, motor delay epilepsy, and autistic features. We have performed an observational trial aimed to psychometrically characterize individuals carrying deletions or pathogenic variants in SHANK3, to eventually build a foundation for a subsequent precision psychiatry clinical trial with vafidemstat, a LSD1 inhibitor in Phase II clinical development.MethodsWe have conducted a pilot study to clinically characterize the profile of 30 subjects, all diagnosed of molecularly confirmed PMS. Subjects were phenotypically characterized by applying different psychometric scales, including Repetitive Behavior Questionnaire (RBQ), Vineland Adaptive Behavior Scales, ADOS-2, the Battelle developmental inventory screening test and the Behavior Problems Inventory (BPI). Nineteen patients were included in the pilot study, followed by additional 11 individuals in the validation set.ResultsUnsupervised hierarchical clustering of the collected psychometric data identifies three groups of patients, with different cognitive and behavioral profile scores. Statistically significant differences in deletion sizes were detected comparing the three clusters (corrected by gender), and the size of the deletion appears to be positively correlated with ADOS and negatively correlated with Vineland-A and -C scores. No correlation was detected between deletion size and the BPI and RBQ scores.DiscussionThis analysis presents new data on the best potential endpoints, for a future clinical study exploring vafidemstat actionability for SHANK3-associated psychiatric disorders, constituting a good example of how Precision Medicine may open new avenues to understand and treat Central Nervous System (CNS) disorders, pioneering individual management in PMS.